Synchronous primary tumors of the endometrium and ovary (Journal of Pathology of Nepal, 2012)
Background: Primary synchronous cancer of the female genital tract is a relatively uncommon. Simultaneously detected endometrial and ovarian malignancies constitute the commonest occurrence. A set of pathological criteria has been described to differentiate synchronous primaries from metastatic tumors. The purpose of this study was to characterize patients with synchronous primary endometrial and ovarian tumors. Materials and Methods: This was a retrospective study done in Department of Pathology, Tribhuwan University Teaching Hospital from September 2006 to August 2011. The datas were retrieved from computer database. Results: There were totally of 10 cases of simultaneously detected endometrial and ovarian cancers. Out of 10 cases, 7 cases were synchronous primary endometrial and ovarian cancers while three were metastatic. Median age at presentation was 47.4 years. Six (85.8%) of these patients presenting with dual primary tumors were premenopausal. Grade 1 histology was seen in 57% of endometrial and 42% of ovarian tumors. Atypical endometrial hyperplasia was found in 42.8% of cases while none of the cases showed endometriosis. Conclusion: Though limited by relatively small number of cases, younger and premenopausal women were predisposed to developing synchronous primary tumors of the endometrium and ovary. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6019 JPN 2012; 2(3): 189-192